High-performance self-supporting silver selenide / carbon composite flexible thermoelectric thin film and preparation and application thereof
By printing silver selenide/carbon composite materials on the polyimide substrate and performing substrate peeling after vacuum annealing, a high-performance self-supported silver selenide/carbon composite flexible thermoelectric film was prepared, solving the problems of low thermoelectric performance and high cost in the prior art, and achieving efficient thermoelectric performance and flexibility.
Patent Information
- Application Number
- CN202411935609.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The existing self-supported flexible thermoelectric film has low thermoelectric properties, high production cost, long time, complex technology, and limited product size, which limits its further application in flexible thermoelectric materials.
The precursor slurry is formed by stirring a mixture of polyvinylpyrrolidone and ethylene glycol with silver selenide powder, and printed on the polyimide substrate by screen printing technology, and the substrate is peeled off after heating and annealing in a vacuum environment to obtain a self-supported silver selenide/carbon composite flexible thermoelectric film.
It realizes the preparation of high-performance self-supported silver selenide/carbon composite flexible thermoelectric films, with excellent thermoelectric properties and flexibility, with room temperature ZT value up to 0.81, can output a high power density at low temperature differences, and exhibit good flexibility, and is suitable for wearable electronic devices.
Smart Images

Figure CN119744108A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thermoelectric material preparation, and relates to a high-performance self-supporting silver selenide / carbon composite flexible thermoelectric film and its preparation and application. Background Art
[0002] With the rapid development of Internet of Things technology and wearable electronic devices, the demand for sustainable energy supply technology and matching functional materials is becoming increasingly urgent. Flexible thermoelectric materials are a type of green functional materials that can continuously use the temperature difference between the human body and the environment to generate electricity. Flexible thermoelectric devices prepared using flexible thermoelectric materials have the advantages of all-solid-state, lightweight, noiseless, small size and maintenance-free, and are easy to integrate into multifunctional microelectronic devices. Therefore, they have broad application prospects in the field of energy supply. The performance of thermoelectric materials is usually evaluated by the dimensionless figure of merit (ZT), which is calculated as follows: ZT = α2σT / κ, where α is the Seebeck coefficient, σ is the electrical conductivity, κ is the thermal conductivity, T is the thermodynamic temperature, and α2σ is called the power factor (PF).
[0003] In recent years, research on flexible thermoelectric materials has gradually increased and has made certain research progress in the direction of flexible thermoelectric films, which can be divided into two types of flexible thermoelectric films: flexible substrate-supported and self-supported. The former usually deposits thermoelectric materials onto a flexible polymer substrate to obtain flexibility. However, the flexible substrate will affect the effective collection of heat and the accurate testing of thermal properties, and the flexible substrate will generate additional stress during the bending process, thereby limiting the flexibility of the composite film. In addition, magnetron sputtering, thermal evaporation, vacuum-assisted filtration and hot pressing technologies have been adopted to obtain high-performance thermoelectric films supported by flexible substrates, but these technologies are costly, energy-intensive, difficult to operate, and cannot be scaled up.
[0004] Self-supporting flexible thermoelectric films are mainly divided into conductive polymer-based materials, carbon-based materials and plastic inorganic films. The former two usually use conductive polymers (such as PEDOT:PSS, etc.) and carbon materials (such as carbon nanotubes, etc.) with excellent mechanical properties as flexible matrices, and then use inorganic thermoelectric materials as fillers to synergistically optimize the thermoelectric performance and flexibility of the composite film by adjusting the ratio of the two phases. However, the intrinsic thermoelectric performance and thermal stability of conductive polymers are poor, while the Seebeck coefficient of carbon materials is low and the thermal conductivity is high. In addition, the large number of heterogeneous interfaces formed after the composite are prone to strong scattering of carriers, resulting in the thermoelectric performance of the composite material is still far lower than that of the bulk thermoelectric material. Plastic inorganic films based on silver sulfide-based materials show excellent ductility, but their thermoelectric performance is generally low and cannot meet the energy supply needs of electronic devices. In addition, their preparation cycle is long and the conditions are harsh, which is not conducive to their commercial application in the field of flexible electronics.
[0005] Silver selenide is a narrow bandgap n-type semiconductor. At low temperatures, silver selenide has an orthorhombic structure and exhibits semiconductor properties. At around 407K, its crystal structure undergoes a phase transition and transforms into a cubic structure, exhibiting superionic conductor properties. Therefore, current research focuses on the near-room temperature performance of silver selenide-based thermoelectric materials. Orthorhombic silver selenide bulk has high electrical conductivity, high mobility and low thermal conductivity, and has excellent near-room temperature thermoelectric properties. However, there are currently few studies on self-supporting silver selenide-based flexible thermoelectric films, and the reported thermoelectric performance is low. In addition, the preparation cost is high, time-consuming, technically complex, and the product size is limited, which limits its further application in flexible thermoelectric materials.
[0006] For example, Chinese patent CN202010607248.X provides a method for preparing a high-performance polyvinyl pyrrolidone / silver selenide / nylon flexible composite thermoelectric film, comprising the following steps: (1) using selenium nanowires as a template, reacting with silver nitrate in an ethylene glycol solvent, adding polyvinyl pyrrolidone during the reaction to obtain a polyvinyl pyrrolidone-coated silver selenide multi-scale nanostructure; (2) dispersing the polyvinyl pyrrolidone-coated silver selenide multi-scale nanostructure in anhydrous ethanol, using a nylon filter membrane as a substrate, filtering, vacuum drying, and hot pressing to obtain the target product, polyvinyl pyrrolidone / silver selenide / nylon composite film. The silver selenide nanostructure synthesized in this patent is greatly affected by environmental conditions, and the polyvinyl pyrrolidone added in the synthesis process does not carbonize after hot pressing and still maintains its insulating properties, which is not conducive to improving electrical properties; at the same time, the prepared flexible film is tightly bonded to the nylon substrate, which not only affects the accurate measurement of thermoelectric properties, but also limits its mechanical flexibility; in addition, the preparation of the film requires relatively expensive hot pressing equipment, which is costly and not conducive to large-scale application. Summary of the invention
[0007] The purpose of the present invention is to provide a high-performance self-supporting silver selenide / carbon composite flexible thermoelectric film and its preparation and application. The prepared self-supporting composite film exhibits excellent thermoelectric properties and flexibility.
[0008] The purpose of the present invention can be achieved by the following technical solutions:
[0009] In one aspect, the present invention provides a method for preparing a high-performance self-supporting silver selenide / carbon composite flexible thermoelectric film, comprising the following steps:
[0010] (1) adding polyvinyl pyrrolidone to ethylene glycol, heating and stirring to obtain a mixed solvent, and then stirring the silver selenide powder and the mixed solvent to obtain a precursor slurry;
[0011] (2) printing the precursor slurry on a polyimide substrate using a screen printing technique and drying the resulting film precursor;
[0012] (3) The thin film precursor is placed in a vacuum environment for heating and annealing, then cooled to room temperature, and the substrate is peeled off to obtain a composite thin film, which is the target product.
[0013] Furthermore, the ratio of the added amount of polyvinyl pyrrolidone to ethylene glycol is (1.5-2.5) g:10 mL, preferably 2 g:100 mL.
[0014] Furthermore, in step (1), the temperature of heating and stirring is 60-80°C, preferably 70°C.
[0015] Furthermore, in step (1), the mass ratio of silver selenide powder to mixed solvent is 6-10:1.
[0016] Furthermore, in step (1), the stirring time of the silver selenide powder and the mixed solvent is 16 to 32 hours, preferably 24 hours.
[0017] Furthermore, in step (2), the mesh size of the screen used in the screen printing technology is 250 meshes.
[0018] Furthermore, in step (3), heating annealing is performed in a tube furnace.
[0019] Furthermore, in step (3), the heating annealing temperature is 400-450°C, preferably 420-450°C, more preferably 450°C, and the time is 2-3h.
[0020] Furthermore, during the heating annealing process, the heating rate is 2.5-5°C / min.
[0021] Furthermore, in step (3), the substrate is peeled off and an edge region with a width of 0.5 to 1.5 mm (preferably about 1 mm) is first cut off.
[0022] Furthermore, the silver selenide is prepared by a one-pot method.
[0023] In a second aspect, the present invention provides a high-performance self-supporting silver selenide / carbon composite flexible thermoelectric film, which is prepared by the preparation method described above.
[0024] In a third aspect, the present invention provides an application of a high-performance self-supporting silver selenide / carbon composite flexible thermoelectric film in a flexible thermoelectric device or a portable wearable electronic device.
[0025] The formation mechanism of the self-supporting silver selenide / carbon composite flexible thermoelectric film is speculated as follows:
[0026] First, polyvinyl pyrrolidone is selected as a binder and mixed with low-boiling ethylene glycol to obtain a solvent with good fluidity and viscosity. The solvent is mixed with silver selenide powder in a certain proportion to obtain an ink with good stability. Then, a simple and scalable screen printing technology is used to print the ink on a polyimide substrate with high thermal stability (the thickness of which is selected to be 150 μm to ensure that it will not be deformed by heat). Then, the printed film is annealed in a vacuum furnace. During the annealing process, the low-boiling ethylene glycol in the film evaporates, and at the same time, the polyvinyl pyrrolidone in the solvent is carbonized, resulting in a gradient distribution of carbon content along the out-of-plane direction. The evaporation of the solvent leaves a small amount of micropores in the film, which helps the film release stress and consume energy during bending. In addition, when the viscous solvent near the smooth surface of the polyimide substrate evaporates, the binding force between the remaining silver selenide / carbon composite film and the polyimide substrate decreases significantly, which makes it easy for the silver selenide / carbon composite film to be peeled off from the polyimide substrate to become a self-supporting film. At the same time, in the initial annealing stage, the escape of the solvent can leave a sedimentation space for the silver selenide grains, and the silver selenide grains grow further with the assistance of the residual fluid solvent and show good crystallinity. The residual polyvinyl pyrrolidone will eventually be pyrolyzed and converted into carbon with low thermal conductivity and attached to the silver selenide grain boundaries. Due to the double blocking of the dense and smooth polyimide substrate and the settled upper silver selenide layer, the silver selenide grains near the bottom of the film tend to grow in a textured manner along the in-plane direction. In contrast, the silver selenide grains on the surface of the film tend to grow freely into equiaxed crystals due to exposure to vacuum. Therefore, the silver selenide grains form a texture gradient from the bottom of the film to the surface, which is conducive to the high flexibility of the composite film. The prepared self-supporting silver selenide / carbon composite film has excellent flexibility and excellent thermoelectric properties.
[0027] The present invention uses a one-pot method to synthesize silver selenide powder, and then mixes it with polyvinyl pyrrolidone and ethylene glycol in a certain proportion to obtain a thermoelectric ink with good fluidity. After that, a scalable screen printing technology is used to print the film, and a self-supporting silver selenide / carbon flexible composite film with high thermoelectric performance and excellent flexibility is prepared through a thermal annealing process and a simple substrate peeling process. Specifically, the silver selenide / carbon composite film has a dense structure, composed of well-crystallized micro-nano-level silver selenide grains and a small amount of carbon, and exhibits a high room temperature PF. At the same time, there are a few pores, multi-size defects and heterogeneous interfaces in the film, resulting in a lower κ of the film, and its room temperature ZT value can reach 0.81. In addition, thanks to the dual gradient combination of carbon content and silver selenide texturing level in the out-of-plane direction, the film exhibits excellent flexibility. The four-arm thermoelectric device assembled with the optimized film outputs a maximum power of 5.5μW and a power of 22.9W m at a temperature difference of 31.4K. -2 high power density and exhibits good flexibility.
[0028] Compared with the prior art, the present invention has the following advantages:
[0029] (1) This preparation process has low cost, the thermoelectric ink (i.e., precursor slurry) is easy to synthesize, and it uses mature screen printing technology and simple thermal annealing process, which has low energy consumption and can be prepared on a large scale;
[0030] (2) The prepared flexible composite film does not require a flexible substrate support, thus avoiding the interface problem between the thermoelectric film and the substrate, which is conducive to the effective collection of heat and the direct and accurate testing of thermoelectric performance;
[0031] (3) In the prepared self-supporting silver selenide / carbon composite film, the silver selenide grains with nanometer to submicron size have good crystallinity and coherent grain boundaries, while a small amount of adhesive carbon exists in the nanopores and / or grain boundaries. In addition, there are multi-size defects, which are conducive to the coordinated optimization of thermoelectric transport properties;
[0032] (4) The prepared film has excellent thermoelectric properties, and the room temperature ZT value (~0.81) of the optimized film is one of the highest values reported so far for self-supporting flexible thermoelectric films;
[0033] (5) The prepared film has a carbon content gradient along the out-of-plane direction and a silver selenide texturing level gradient. The dual gradients together construct the flexible structure of the self-supporting film. The small amount of micropores in the film is also conducive to releasing the bending stress. Therefore, the composite film exhibits excellent flexibility and can withstand 3000 bending cycles at a bending radius of 4 mm while maintaining a conductivity of more than 90%;
[0034] (6) The flexible thermoelectric device prepared with this film has excellent performance and can output a high power density under low temperature difference. The device has good flexibility and can be used for heat collection and power generation in wearable electronic devices in different scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 Field emission scanning electron microscope (FESEM) images of the surface and back side of the sample film1 prepared in Example 1.
[0036] Figure 2 The FESEM image of the cross section of the sample film1 prepared in Example 1 and the corresponding EDS energy spectra of C, Ag, and Se elements.
[0037] Figure 3 The X-ray diffraction (XRD) patterns of the surface and back of the sample film 1 prepared in Example 1.
[0038] Figure 4 X-ray photoelectron spectroscopy (XPS) of the surface of sample film1 prepared in Example 1 within a 90 nm depth range and on the back side.
[0039] Figure 5 This is the Raman spectrum at different depths from the bottom to the surface on the cross section of the sample film1 prepared in Example 1.
[0040] Figure 6 Transmission electron microscopy (TEM) images of sample film1 prepared in Example 1 at different resolutions.
[0041] Figure 7 The temperature-dependent thermoelectric performance diagram of the sample film 1 prepared in Example 1 and the comparison of its ZT value with the ZT values of self-supporting flexible thermoelectric films reported in other literatures.
[0042] Figure 8 The flexibility test results of sample film 1 prepared in Example 1 and the flexibility comparison with other flexible thermoelectric films reported in the literature are shown.
[0043] Fig. 9 Output performance of the four-arm flexible thermoelectric device assembled with sample film1 prepared in Example 1.
[0044] Fig.10 The flexibility of the four-arm flexible thermoelectric device assembled with sample film1 prepared in Example 1. DETAILED DESCRIPTION
[0045] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0046] In the following embodiments, the flexible polyimide substrates were purchased from Zhongshan Chenxi Technology Co., Ltd. The rest of the raw materials or processing techniques, unless otherwise specified, are conventional commercially available raw materials or conventional processing techniques in the art.
[0047] Embodiment 1:
[0048] A method for preparing a high-performance self-supporting silver selenide / carbon composite flexible thermoelectric film, the method comprising slowly adding 0.005 mol of silver nitrate, 0.025 mol of potassium hydroxide, 1 mL of 3-mercaptopropionic acid, 0.005 mol of selenium dioxide, and 0.015 mol of potassium borohydride to 500 mL of deionized water in sequence, and then stirring and reacting in a 40°C oil bath for 5 hours. Afterwards, the precipitate is alternately centrifuged and washed twice with deionized water and anhydrous ethanol, and then placed in a vacuum drying oven and dried at 60°C for 12 hours, and then taken out and ground to obtain silver selenide powder.
[0049] Polyvinyl pyrrolidone (PVP-K30) and ethylene glycol were heated and stirred at 70°C for 30 minutes in a ratio of 2g:10mL, and then naturally cooled to room temperature to obtain a solvent. Then, silver selenide powder and solvent were mixed and stirred at a mass ratio of 8:1 for 24 hours, and printed on a flexible polyimide substrate with a thickness of 150μm through a screen with a mesh size of 250 mesh, and then dried in a vacuum drying oven at 60°C for 12 hours. After taking it out, place it in a porcelain boat and put it into a tube furnace, and anneal it at 450°C for 2 hours under a vacuum environment. After the tube furnace is naturally cooled to room temperature, take out the sample and subtract an area of about 1mm wide at the edge of the film, then peel off and remove the polyimide substrate, and a self-supporting silver selenide / carbon composite flexible thermoelectric film (film1) with a film thickness of about 13μm is obtained.
[0050] Figure 1 The field emission scanning electron microscope (FESEM) images of the surface and back of sample film1 are shown. The surface morphology of the film is relatively rough, the grains are equiaxed and contain a small number of micropores. In contrast, the back of the film is relatively smooth and dense, which may be due to the growth of silver selenide grains along the c-axis on the smooth and dense surface of the polyimide substrate. In addition, Figure 2 As shown in Figure 1, the cross-sectional FESEM image of the sample film1 with a thickness of about 13 μm shows weak texture characteristics along the plane direction. In the EDS energy spectrum corresponding to the cross-sectional FESEM image, the C element shows a gradient content change, forming a carbon-rich layer near the film surface, while the Ag and Se elements are relatively evenly distributed. The X-ray diffraction patterns (XRD) of the film surface and back are shown in Figure 1. Figure 3 As shown, it matches well with the standard PDF card (PDF#24-1041) of the orthorhombic phase of silver selenide. In addition, there is a hump in the XRD spectrum of the film surface, which can be attributed to the presence of amorphous carbon. In addition, the intensity of this peak is higher than that of the XRD spectrum of the back of the film, which is related to the higher carbon content on the surface of the film than at the bottom of the film. At the same time, the intensity of the (00l) diffraction peak containing the (002) and (004) planes in the XRD spectrum of the back of the film is enhanced at the same time compared with the surface of the film, indicating that the (00l) texture degree of the silver selenide grains at the bottom of the film is higher than that on the surface of the film. The X-ray photoelectron spectrum (XPS) of sample film1 within a depth range of 90nm was obtained by in-situ etching technology, which is common with the XPS spectrum of the back of the film. Figure 4 As the depth increases, the O 1s peak intensity decreases rapidly, indicating that the oxidation level below the film surface is suppressed. Importantly, the peak position of Ag 3d remains essentially unchanged, indicating that silver selenide with a stoichiometric ratio exists stably in the composite film. The relative intensity of the Ag 3d peak gradually increases, indicating that the content of silver selenide gradually increases, and the carbon content gradually decreases from the surface of the film to the bottom of the film. Raman spectroscopy measurements were performed on the cross section of sample film1 from the bottom to the surface, and the results are shown in Figure 5As shown. Located at 1350 and 1580cm -1 The two nearby peaks belong to the D band and the G band, which are related to carbon defects and graphitization. The other peak at 2580 cm -1 The left and right broad peaks correspond to 2D bands, which are caused by the accumulation of trace graphitized carbon. The three characteristic peaks of carbon indicate that polyvinyl pyrrolidone is carbonized during annealing. It is worth noting that under the same laser light source and light intensity, the detection intensity of these characteristic peaks gradually increases from the bottom of the film to the surface of the film, indicating that the carbon content gradually increases along the out-of-plane direction.
[0051] Figure 6 (a) shows a low-magnification transmission electron microscopy (TEM) image of a typical area of sample film 1, which contains dense silver selenide polycrystals and fewer nanopores. Figure 6 (b) shows Figure 6 High-resolution TEM (HRTEM) image of the area marked by the red box in (a), which contains several silver selenide grains surrounded by a nanometer-thick carbon layer. Figure 6 (c) Yes Figure 6 A magnified image of the lattice distorted region marked by a brown square in (b), which exhibits typical stacking fault (SFs) features, resulting in a slight pattern overlap of the fast Fourier transform (FFT) pattern in the upper left inset. Another inverse Fourier transform image shows the presence of edge dislocations. These localized lattice defects enhance the scattering of phonons, thereby reducing κ. Figure 6 (d) shows Figure 6 The more ordered lattice arrangement region marked by the green square in (b) shows three silver selenide nanograins with coherent grain boundaries (GBs), which facilitate electron transport while hindering phonon propagation. Figure 6 (d) In the corresponding FFT image, the presence of amorphous rings indicates that there is a trace amount of amorphous carbon inside the silver selenide grains. Figure 6 As shown in (e), carbon adheres around GBs and not only tightly binds to the silver selenide grains, but also fills and heals some large cracks between the grains, thus helping the silver selenide / carbon composite film to withstand external stress and thus exhibit good mechanical properties. Figure 6 (e) The enlarged image of the carbon coating area marked by the blue box ( Figure 6 In (f), a small amount of ordered stripes appear at the edges of the silver selenide grains, indicating that the carbon is slightly graphitized.
[0052] Figure 7 The temperature-dependent thermoelectric properties of sample film 1 are shown. Its room temperature Seebeck coefficient is -138 μVK -1 , conductivity is 930S cm -1 , the power factor is 1761μW m-1 K -2 .like Figure 7 As shown in (a), when the temperature increases from 300K to 400K, |α| increases from 138μV K -1 Down to 82μV K -1 , σ is from 930μV K -1 Rapidly rise to 2743S cm -1 , which is due to the thermal excitation of carriers in the orthorhombic silver selenide semiconductor (β-Ag2Se). However, when the temperature reaches 410K, |α| decreases rapidly to 28μV K -1 , and σ suddenly increases to 3635S cm -1 This is because β-Ag2Se transforms into cubic silver selenide (α-Ag2Se) at around 407K (Tc), which has typical semi-metallic characteristics. Finally, the sample film1 achieves a maximum PF of 1955μW m at about 360K. -1 K -2 Considering the strong coupling between electrical properties and carrier concentration (n), Figure 7 (b) shows the temperature dependence of n and carrier mobility (μ) of sample film1. As the temperature increases, n increases from 0.6×10 19 cm -3 Gradually increased to 2.8×10 19 cm -3 , μ is reduced from 968 to 615 cm 2 V -1 s -1 When the temperature exceeds Tc, n and μ drop to 7.0×10 19 cm -3 and 288cm 2 V -1 s -1 This sudden change is due to the fact that α-Ag2Se is a superionic conductor in which Ag ions move freely and the ion diffusion coefficient is high, which causes strong electron scattering and a sudden drop in μ. The κ value of the film1 film with a thickness of about 13 μm at room temperature is 0.66 W m -1 K -1 After calculation, the room temperature ZT value of sample film1 is 0.81, as shown in Figure 7 (c) shows that this value is one of the highest ZT values reported in the literature for free-standing flexible thermoelectric films.
[0053] The flexibility of sample film1 is as follows Figure 8(a) When sample film 1 was bent 1000 times with a bending radius of 4 mm, its σ value only decreased by 2.8%. As the number of bends increased to 3000 times, the σ retention rate still exceeded 90%, showing excellent flexibility. Figure 8 As shown in (b), the flexibility exhibited by sample film1 is competitive with the flexible films (including substrate-supported films and self-supporting films) reported in the literature (such as Nat. Mater. 2019, 18, 62; Adv. Funct. Mater. 2022, 32, 2106902).
[0054] Fig. 9 The output characteristics of the four-arm flexible thermoelectric device assembled with sample film1 are shown. The open circuit voltage (V oc ) is linearly related to the temperature difference between the hot and cold ends of the device and is close to the theoretical open circuit voltage. L ), the output voltage (V) and output current (I) show a linear relationship under different temperature differences. L When the total internal resistance (Ri) of the circuit is equal, the maximum output power is 2.0, 3.1 and 5.5 μW at ΔT of 18.5, 24.7 and 31.4 K, respectively, and the corresponding power density is 8.2, 13.1 and 22.9 W m -2 , showing excellent output characteristics. In addition, the flexibility of the prepared thermoelectric device was tested by bending along the directions parallel (x-x') and perpendicular (y-y') to the arm length direction. The device was directly clamped with a polyimide film to avoid additional damage.
[0055] like Fig.10 As shown in the figure, no matter it is bent in the x-x' direction or in the y-y' direction, the resistance change of the device when it is bent along a round tube with a radius of 9 mm is greater than the resistance change of 18 mm. This is because the smaller the bending radius, the greater the bending stress. When the bending radius is 9 mm, after bending 1000 times along the x-x' or y-y' direction, the resistance change rate is 10.7% and 11.0%, respectively, indicating that the prepared thermoelectric device has good flexibility.
[0056] Embodiment 2:
[0057] Compared with Example 1, most of the above are the same, except that the weight ratio of silver selenide powder to solvent is adjusted to 6:1. The room temperature Seebeck coefficient of the prepared self-supporting flexible composite film is -137 μV K -1 , conductivity is 798Scm -1 , the power factor is 1491μW m -1 K -2 The reduction in its thermoelectric performance is mainly due to the evaporation of more solvents, which leads to an increase in pores and thus poor electrical performance.
[0058] Embodiment 3:
[0059] Compared with Example 1, most of the above are the same, except that the weight ratio of silver selenide powder to solvent is adjusted to 10:1. The room temperature Seebeck coefficient of the prepared flexible composite film is -133 μV K -1 , conductivity is 901S cm -1 , the power factor is 1591μW m -1 K -2 , which is at a relatively high level among the power factors of self-supporting flexible thermoelectric films reported so far.
[0060] Comparative Example 1:
[0061] Compared with Example 1, most of the above are the same, except that the thermal annealing temperature is adjusted to 400°C. The room temperature Seebeck coefficient of the prepared self-supporting silver selenide / carbon composite flexible film is -135 μV K -1 , conductivity is 831S cm -1 , the power factor is 1524μW m -1 K -2 The decrease in its thermoelectric performance is mainly due to the incomplete removal of solvents caused by the lower heat treatment temperature, the smaller grain size of silver selenide, and the higher defect content in the carbonized product of polyvinyl pyrrolidone after the heat treatment temperature is reduced, which leads to enhanced scattering of carriers and thus a decrease in electrical performance.
[0062] Comparative Example 2:
[0063] Compared with Example 1, most of the aspects are the same, except that the flexible polyimide substrate is replaced by a nylon substrate. The nylon substrate will curl and deform at a heat treatment temperature above 250° C., resulting in film failure.
[0064] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing a high-performance self-supporting silver selenide / carbon composite flexible thermoelectric film, characterized in that: The following steps are involved: (1) adding polyvinyl pyrrolidone to ethylene glycol, heating and stirring to obtain a mixed solvent, and then stirring the silver selenide powder and the mixed solvent to obtain a precursor slurry; (2) printing the precursor slurry on a polyimide substrate using a screen printing technique and drying the resulting film precursor; (3) The thin film precursor is placed in a vacuum environment for heating and annealing, then cooled to room temperature, and the substrate is peeled off to obtain a composite thin film, which is the target product.
2. The method for preparing a high-performance self-supporting silver selenide / carbon composite flexible thermoelectric film according to claim 1, characterized in that: The ratio of the added amount of polyvinyl pyrrolidone to ethylene glycol is (1.5-2.5) g:10 mL.
3. The method for preparing a high-performance self-supporting silver selenide / carbon composite flexible thermoelectric film according to claim 1, characterized in that: In step (1), the temperature of heating and stirring is 60 to 80°C.
4. The method for preparing a high-performance self-supporting silver selenide / carbon composite flexible thermoelectric film according to claim 1, characterized in that: In step (1), the mass ratio of silver selenide powder to mixed solvent is 6-10:
1.
5. The method for preparing a high-performance self-supporting silver selenide / carbon composite flexible thermoelectric film according to claim 1, characterized in that: In step (1), the stirring time of the silver selenide powder and the mixed solvent is 16 to 32 hours.
6. The method for preparing a high-performance self-supporting silver selenide / carbon composite flexible thermoelectric film according to claim 1, characterized in that: In step (2), the mesh size of the screen used in the screen printing technology is 250 meshes.
7. The method for preparing a high-performance self-supporting silver selenide / carbon composite flexible thermoelectric film according to claim 1, characterized in that: In step (3), the substrate is peeled off and an edge region with a width of 0.5 to 1.5 mm is first cut off.
8. The method for preparing a high-performance self-supporting silver selenide / carbon composite flexible thermoelectric film according to claim 1, characterized in that: In step (3), the heating annealing temperature is 400-450° C. and the time is 2-3 hours.
9. A high-performance self-supporting silver selenide / carbon composite flexible thermoelectric film, characterized in that: The method is prepared according to any one of claims 1 to 8.
10. Application of the high-performance self-supporting silver selenide / carbon composite flexible thermoelectric film as claimed in claim 9 in flexible thermoelectric devices or portable wearable electronic devices.
Citation Information
Patent Citations
Method for preparing high-performance polyvinylpyrrolidone / silver selenide / nylon flexible composite thermoelectric film
CN111864045A
Novel germanium telluride based thermo-electric material with high thermo-electric performance and preparation method thereof
CN112661122A
Flexible silver selenide-based thermoelectric thin film and preparation method thereof
CN113097375A
Method for preparing high-performance polypyrrole / silver selenide / nylon flexible composite thermoelectric thin film
CN114005927A
Flexible photo-thermal electric detection device based on spraying method and preparation method of flexible photo-thermal electric detection device
CN117812985A